Aplicação de espectroscopia de impedância no estudo de blendas de biodiesel/diesel - Silveira, Luiz Gustavo Davanse da (2010)
In this work, biodiesel/diesel blends, with concentrations of methyl soyate between 0 and 100% have been prepared and studied by impedance spectroscopy. Nuclear magnetic resonance spectroscopy (1H-NMR) and infrared spectroscopy (FTIR) were also used to identify samples' compositions and quantify methyl esters in the samples. The NMR and FTIR results have showed that a high concentration of non transesterified feedstock (from 25% to 30%) was present in the biodiesel sample. Impedance spectroscopy results showed that │Z│assumes lower values for samples with higher biodiesel concentration. A equivalent circuit composed by two parallel RC circuits in series has been used in data analysis. This model implies the existence of two dipolar relaxation processes happening in the samples. It is believed that the orientation of methyl ester molecules and acylglicerols are responsible for this behavior. It has also been observed that the diferences between samples' spectra are more prominent at low frequencies (20 Hz to 1kHz). In this frequency range the complex impedance of samples containing high concentrations o petrodiesel tend to deviate from the behavior of the equivalent circuit. This comportment suggests that a phenomenon related to diesel constituents may takes places at low frequencies. However, more research is needed in order to clarify the origin of the observed behavior. Finally, it has been possible to develop an empirical model that correlates impedance and biodiesel concentration in the samples. However, other studies should be conducted in order to attest the veracity and applicability of this empirical model.